Implementasi Akad Salam Dalam Pembiayaan Sektor Pertanian Oleh Bank Syariah - Nurmaini, Nurmaini; Winario, Mohd; Mairiza, Diany (EL-EMIR Institute, 2025)
The implementation of the Salam contract in agricultural financing by Islamic banks in Indonesia serves as an alternative financing method aligned with Sharia principles. The Salam contract is a type of sale in which payment is made in advance, while the goods are delivered at a later date. This model is highly relevant in the agricultural context, as farmers require working capital before the harvest period. This study focuses on how Islamic financial institutions apply the Salam contract to support the agricultural sector, starting from the identification of farmers' needs, determination of price and product specifications, payment mechanisms, to the distribution of agricultural products. The challenges faced by Islamic banks in implementing the Salam contract include commodity price fluctuations, crop failure risks, uncertainty in harvest time, and limited risk management capacity. Furthermore, this study evaluates the extent to which the Salam contract instrument can address farmers' needs for fast, easy, and interest-free (riba-free) financing, as well as its contribution to enhancing national agricultural productivity.